2019
DOI: 10.2485/jhtb.28.13
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cell Adhesion and Osseointegration on Anodic Oxidation Modified Titanium Implant Surface

Abstract: Although titanium material is currently widely used in dental and orthopedic application, the bio-inertness of Ti impairs its further use. We previously reported the good bioactivity and biocompatibility of TiO 2 nanotube layer fabricated by anodic oxidation technique using in vitro tests. In the present work, we further clarify the cell adhesion and osseointegration properties of anodized surface through both in vitro and in vivo tests. After anodic oxidation (AO), the structure of nanotubes was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The surface topography of the implant also affects cell characteristics. The nano-surface will alter the adhesion, motility, spread, proliferation, and differentiation of cells [1,10,29,30]. The nano-surface can also influence cell adhesion selectively, which is why osteoblast adhesion was more than fibroblast [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface topography of the implant also affects cell characteristics. The nano-surface will alter the adhesion, motility, spread, proliferation, and differentiation of cells [1,10,29,30]. The nano-surface can also influence cell adhesion selectively, which is why osteoblast adhesion was more than fibroblast [30].…”
Section: Discussionmentioning
confidence: 99%
“…The success rate of dental implants depends on osseointegration, which is initiated by cell adhesion when the implant surface meets the surrounding tissue [1][2][3][4][5][6][7]. Osseointegration failure is characterized by the instability or loosening of the implant, periimplantitis, and bone resorption [1,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoscale structure hastened the growth rate of MC3T3-E1 osteoblastic cells by up to 300% to 400%. Several studies [149,174,185,187,192,194,195] also found that cells attached to the surface of nanotubes became increasingly elongated and formed small filopodia, suggesting that they could be used for orthopedic purposes. Over the years, several researchers [144,188,190,192,193,196] have found that the surfaces of TiO 2 nanotubes immersed in simulated body fluid (SBF) favor the formation of osteoblast-like hydroxyapatite, which is critical for osseointegration, with strong adhesion and binding [230,231].…”
Section: Studies Of the Biological Properties Of Nanostructured Tio 2mentioning
confidence: 99%
“…The results indicated that TiO 2 nanotubes were uniform and caused no inflammation, and that the tissue was normal and healthy. Li et al [187] evaluated the behavior of MC3T3-E1 osteoblasts in experiments with Sprague Dawley rats. After 4 weeks they observed that the anodized implant surface promoted osseointegration.…”
Section: Studies Of the Biological Properties Of Nanostructured Tio 2mentioning
confidence: 99%